2014
DOI: 10.1189/jlb.2a0314-178r
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 regulates Aicda expression through miR-155

Abstract: Aicda is a critical component of antibody class-switching in B cells. In this work, we study the impact of TLR4 activation and IL-10 stimulation on Aicda expression in B cells. Through the global analysis of miRNAs in response to TLR4 activation, in combination with IL-10 stimulation, we identified that IL-10 can suppress TLR4-induced miR-155 expression, an effect that resulted in enhanced Aicda expression. Furthermore, when preventing miR-155 control of Aicda expression, by genetic mutation of its target site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…This is consistent with our finding that NE inhibitors stimulate IL-10 expression, but also BAFF and APRIL in cultures of splenocytes. IL-10 was reported to regulate expression of AID for induction of Ig CSR [19] and it is wellestablished that IL-10 facilitates Ig class switching for production of IgA [20]. Thus, our data suggest that NE inhibitors stimulate antibody production through stimulation of AID and inhibition of the activation/degradation of cytokines and cytokine receptors by elastase.…”
Section: The Neutrophil Elastase Inhibitors Stimulate Cytokine Signalsupporting
confidence: 57%
“…This is consistent with our finding that NE inhibitors stimulate IL-10 expression, but also BAFF and APRIL in cultures of splenocytes. IL-10 was reported to regulate expression of AID for induction of Ig CSR [19] and it is wellestablished that IL-10 facilitates Ig class switching for production of IgA [20]. Thus, our data suggest that NE inhibitors stimulate antibody production through stimulation of AID and inhibition of the activation/degradation of cytokines and cytokine receptors by elastase.…”
Section: The Neutrophil Elastase Inhibitors Stimulate Cytokine Signalsupporting
confidence: 57%
“…It is unknown which miR-155 targets and pathways are most relevant to our observations, but it is likely that this miR has a cumulative effect on immunity and infection. Recent published findings have shown that miR-155 regulation of AID is important for IL-10-mediated regulation of B cell activation [ 53 ]. Also, SHIP1 was shown to be repressed by miR-155 in BMDMs [ 40 ], which is reversed with the addition of IL-10 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that miRNAs are also important in the regulation of the immune system. miRNA regulate the production of multiple proinflammatory molecules, such as cytokines at the post-transcriptional level (Fairfax et al, 2015, Quinn and O'Neill, 2014, Hou et al, 2009. miRNAs act to fine-tune the immune system so that the inflammatory response is tightly controlled.…”
Section: Discussionmentioning
confidence: 99%